THE EFFECT OF FINANCIAL LITERACY AND FINTECH USAGE ON STUDENTS’ CONSUMPTIVE BEHAVIOR WITH SELF-EFFICACY AS A MEDIATING VARIABLE - Abdurrohman; Abdul Wahid Alfarizi; Bambang Hermawan; Priatna Wijaya; Ahmad Solihin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The rapid growth of financial technology has reshaped students’ financial behavior through the widespread use of digital payment systems. This study examines the effects of financial literacy and fintech usage on students’ consumptive behavior, with financial self‑efficacy as a mediating variable. Using a quantitative explanatory approach, data were collected from 259 vocational high school students and analyzed with PLS‑SEM. The results show that financial literacy significantly reduces consumptive behavior, while fintech usage significantly increases it. Although financial literacy enhances financial self‑efficacy, self‑efficacy does not significantly influence consumptive behavior nor mediate the tested relationships. These findings indicate that technological convenience outweighs psychological control, highlighting the importance of integrating financial literacy education with behavioral regulation in the digital finance environment.